The low-density lipoprotein receptor-related protein 1 and amyloid-β clearance in Alzheimer’s disease - Kanekiyo, Takahisa; Bu, Guojun (Frontiers in Aging Neuroscience, 2014)
Accumulation and aggregation of amyloid-β (Aβ) peptides in the brain trigger the development of progressive neurodegeneration and dementia associated with Alzheimer’s disease (AD). Perturbation in Aβ clearance, rather than Aβ production, is likely the cause of sporadic, late-onset AD, which accounts for the majority of AD cases. Since cellular uptake and subsequent degradation constitute a major Aβ clearance pathway, the receptor-mediated endocytosis of Aβ has been intensely investigated. Among Aβ receptors, the low-density lipoprotein receptor-related protein 1 (LRP1) is one of the most studied receptors. LRP1 is a large endocytic receptor for more than 40 ligands, including apolipoprotein E (apoE), α2-macroglobulin and Aβ. Emerging in vitro and in vivo evidence demonstrates that LRP1 is critically involved in brain Aβ clearance. LRP1 is highly expressed in a variety of cell types in the brain including neurons, vascular cells and glial cells, where LRP1 functions to maintain brain homeostasis and control Aβ metabolism. LRP1-mediated endocytosis regulates cellular Aβ uptake by binding to Aβ either directly or indirectly through its co-receptors or ligands. Furthermore, LRP1 regulates several signaling pathways, which also likely influences Aβ endocytic pathways. In this review, we discuss how LRP1 regulates the brain Aβ clearance and how this unique endocytic receptor participates in AD pathogenesis. Understanding of the mechanisms underlying LRP1-mediated Aβ clearance should enable the rational design of novel diagnostic and therapeutic strategies for AD.